Amphiphilic hydrogel electrolyte of aqueous zinc ion battery as well as preparation and application of amphiphilic hydrogel electrolyte

By using amphiphilic hydrogel electrolyte in aqueous zinc ion batteries to regulate the cationic state and embedded reaction, the problem of incomplete clear reaction mechanism in existing batteries is solved, and the window for high energy density and electrochemical stability is widened.

CN119495834APending Publication Date: 2025-02-21CHINA NAT PETROLEUM CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311047005.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-20
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

The chemical reaction mechanisms of existing aqueous zinc ion batteries in MnO2/Mn2+ conversion and Zn2+/H+ embedded/deintercalation are not completely clear, which affects the improvement of battery performance.

Method used

Using amphiphilic hydrogel electrolyte, the hydrophobic chain segments are crosslinked in the hydrophilic chain segments of the hydrogel electrolyte, the cationic state is regulated, the interaction between hydrophilic functional groups and water molecules is enhanced, and the intercalation of zinc ions and hydrogen ions is regulated. Transformation reaction.

Benefits of technology

The electrochemical stability window of electrolytes is broadened, and the high-voltage manganese dioxide deposition and dissolution conversion reaction is realized, the intercalation and conversion reaction efficiency of zinc ions and hydrogen ions is improved, and the energy density of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495834A_ABST
    Figure CN119495834A_ABST
Patent Text Reader

Abstract

The invention discloses an amphiphilic hydrogel electrolyte of an aqueous zinc ion battery. A hydrophobic chain segment is crosslinked on a hydrophilic chain segment of the hydrogel electrolyte. The invention also discloses a preparation method and application thereof. The amphiphilic hydrogel electrolyte can enhance the interaction between a hydrophilic functional group and water molecules, has a wide electrochemical stability window, allows high-voltage scanning, and can activate a MnO2 / Mn < 2 + > redox conversion reaction in a high discharge platform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an amphiphilic hydrogel electrolyte for an aqueous zinc ion battery and a preparation method and application thereof. Background Art

[0002] Wind, solar, tidal and other power generation are unstable due to their own periodicity, volatility, and seasonality, resulting in a large amount of electricity waste and loss. It is necessary to develop energy storage technology to solve such problems. At present, the mainstream battery technology is represented by lithium-ion batteries with organic electrolyte systems. However, the flammable and toxic organic electrolytes used in organic electrolyte system lithium-ion batteries have safety hazards such as fire and explosion, and are difficult to use in scenarios with high safety requirements. The scarce lithium resources and the high price of lithium metal lead to high costs of organic lithium-ion batteries.

[0003] Aqueous zinc-ion batteries use aqueous electrolytes and zinc as the negative electrode, which has certain technical advantages. On the one hand, metallic zinc reserves are abundant, cost-effective, and have high theoretical capacity and low electrochemical reaction potential; on the other hand, aqueous electrolytes are safe and will not catch fire or explode even in extremely harsh operating environments, such as knocking, puncture, and fire. Among the many aqueous zinc-ion battery systems under research, rechargeable aqueous Zn||MnO2 batteries have been widely studied, but the electrochemical reaction mechanism behind them, especially in MnO2 / Mn 2+ Conversion and Zn 2+ / H + The intercalation / deintercalation chemical reactions are still not fully understood, which affects the further improvement of battery performance. Summary of the invention

[0004] The present invention is made in order to achieve precise control of cation conversion and embedding performance in aqueous zinc ion batteries.

[0005] As one aspect of the present invention, it relates to an amphiphilic hydrogel electrolyte for an aqueous zinc ion battery, wherein a hydrophilic segment of the hydrogel electrolyte is cross-linked with a hydrophobic segment.

[0006] In a specific embodiment, the hydrophilic segment refers to polyacrylamide.

[0007] In a specific embodiment, the hydrophobic segment refers to polyoctadecyl methacrylate.

[0008] As another aspect of the present invention, it relates to a method for preparing the above-mentioned aqueous zinc ion battery amphiphilic hydrogel electrolyte, comprising:

[0009] 1) dissolving the hydrophobic polymer chain monomer and the hydrophilic molecular chain monomer in a cationic salt solution containing a surfactant in sequence;

[0010] 2) adding a crosslinking agent and a thermal initiator in sequence;

[0011] 3) sealing and heating the reaction to obtain a hydrogel;

[0012] 4) placing the hydrogel prepared in 3) in a mixed solution of zinc ions and manganese ions to obtain an amphiphilic hydrogel electrolyte.

[0013] In a specific embodiment, the hydrophobic polymer chain monomer refers to octadecyl methacrylate, the hydrophilic molecular chain monomer refers to acrylamide, the surfactant refers to hexadecylpyridinium chloride monohydrate, the cationic salt refers to zinc sulfate, the cross-linking agent refers to N,N-methylenebisacrylamide, the thermal initiator refers to ammonium persulfate, the heating temperature is 30-80°C, and the reaction time is 1-3h.

[0014] The mass ratio of the hydrophobic polymer chain monomer, the hydrophilic molecular chain monomer, the surfactant, the cross-linking agent and the thermal initiator is 0.20-0.40:1.5-3.0:2.0-4.0:0.003:0.08.

[0015] As another aspect of the present invention, it relates to an aqueous zinc ion battery, which uses the above-mentioned aqueous zinc ion battery amphiphilic hydrogel electrolyte as electrolyte.

[0016] In a specific embodiment, the aqueous zinc ion battery uses metal zinc foil as the negative electrode and manganese dioxide as the positive electrode.

[0017] The amphiphilic hydrogel electrolyte provided in the embodiment of the present invention can regulate the cationic state at the electrode interface and mainly plays the following two roles (refer to Figure 1 ): On the one hand, it enhances the interaction between hydrophilic functional groups and water molecules, inhibits the activity of free water molecules, thereby broadening the electrochemical stability window of the electrolyte and realizing the high-voltage manganese dioxide deposition dissolution conversion reaction; on the other hand, the gel electrolyte can regulate zinc ions and hydrogen ions, which is conducive to better realizing the embedding and conversion reaction of zinc ions and hydrogen ions. The above functions of amphiphilic hydrogel electrolytes lay the foundation for the development of high-energy-density aqueous zinc-ion batteries.

[0018] The amphiphilic hydrogel electrolyte can enhance the interaction between hydrophilic functional groups and water molecules and has a wide electrochemical stability window (ESWs), allowing high-voltage scanning and activating MnO2 / Mn in a high discharge platform (>1.5 V). 2+ Redox conversion reaction. The amphiphilic hydrogel electrolyte can realize the conversion of manganese ions at high voltage and can precisely regulate the embedding and conversion behavior of zinc ions and hydrogen ions. The selected surfactant helps Zn 2+ Intercalation occurs only at a specific reaction potential, making it+ The electrochemical reaction is separated, thereby improving the energy density of zinc-based batteries. The hydrophobic association between the cathode and the hydrophobic chain in the amphiphilic hydrogel electrolyte can improve the utilization rate of MnO2 and anchor HCCM on the surface of MnO2 particles, thereby achieving excellent regulation of zinc ions at a specific potential. It has the advantage of low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 :Mechanism diagram of amphiphilic hydrogel regulating water molecules and interfacial cations in electrolytes. DETAILED DESCRIPTION

[0020] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0021] In the embodiment of the present invention, the mechanism of the amphiphilic hydrogel regulating water molecules and interfacial cations in the electrolyte can be referred to Figure 1 .

[0022] Example 1

[0023] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof, the steps are as follows:

[0024] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0025] (2) dissolving 2.12 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 30 mL of L A solution at 100° C. to obtain solution B;

[0026] (3) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0027] (4) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0028] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D, cooling to room temperature, and obtaining a mixture E;

[0029] (6) adding 0.08 g of ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0030] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0031] (8) placing the prepared hydrogel G in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4 to finally obtain an amphiphilic hydrogel electrolyte I, which is named 1-PAM-HCCM-C18;

[0032] (9) Using the obtained 1-PAM-HCCM-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0033] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0034] The negative electrode is a zinc foil negative electrode.

[0035] Example 2

[0036] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof. The difference from Embodiment 1 is that the hydrophobic monomer, the hydrophilic monomer, the mass of the surfactant feed, and the volume of the cationic salt are different from those in Embodiment 1. The specific steps are as follows:

[0037] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0038] (2) dissolving 3.02 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 45 mL of L-A solution at 100° C. to obtain solution B;

[0039] (3) adding 0.32 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0040] (4) adding 2.0 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0041] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0042] (6) adding 0.08 g of ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0043] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0044] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named 2-PAM-HCCM-C18;

[0045] (9) Using the obtained 2-PAM-HCCM-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0046] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0047] The negative electrode is a zinc foil negative electrode.

[0048] Example 3

[0049] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof. The difference from Embodiment 1 is that the mass of the hydrophobic monomer, the hydrophilic monomer, and the surfactant are different from those in Embodiment 1 and Embodiment 2. The specific steps are as follows:

[0050] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0051] (2) dissolving 3.92 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 60 mL of L-A solution at 100° C. to obtain solution B;

[0052] (3) adding 0.39 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0053] (4) adding 3.0 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0054] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0055] (6) adding 0.08 g of ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0056] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0057] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named 3-PAM-HCCM-C18;

[0058] (9) Using the obtained 3-PAM-HCCM-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0059] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0060] The negative electrode is a zinc foil negative electrode.

[0061] Example 4

[0062] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof, which differs from Embodiment 1 in that the reaction temperature and reaction time are different. The specific steps are as follows:

[0063] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0064] (2) dissolving 2.12 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 30 mL of L A solution at 100° C. to obtain solution B;

[0065] (3) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0066] (4) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0067] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0068] (6) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0069] (7) Pour F into a sealed mold and place the entire mold in an oven at 50 °C for 2 h to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0070] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named 4-PAM-HCCM-C18;

[0071] (9) Using the obtained 4-PAM-HCCM-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0072] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0073] The negative electrode is a zinc foil negative electrode.

[0074] Example 5

[0075] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof, which differs from Embodiment 1 and Embodiment 4 in that the reaction temperature and reaction time are different. The specific steps are as follows:

[0076] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0077] (2) dissolving 2.12 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 30 mL of L A solution at 100° C. to obtain solution B;

[0078] (3) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0079] (4) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0080] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0081] (6) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0082] (7) Pour F into a sealed mold and place the entire mold in an oven at 30 °C for 3 h to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0083] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named 5-PAM-HCCM-C18;

[0084] (9) Using the obtained 5-PAM-HCCM-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0085] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0086] The negative electrode is a zinc foil negative electrode.

[0087] Comparative Example 1

[0088] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof. The difference from Embodiment 1 is that the hydrophilic monomer used is sulfobetaine methacrylate (SBMA), and the hydrophobic monomer used is trifluoroethyl methacrylate (3FMA). The specific steps are as follows:

[0089] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0090] (2) dissolving 2.12 g of hexadecylpyridinium chloride monohydrate (HCCM) surfactant in 30 mL of L A solution at 100° C. to obtain solution B;

[0091] (3) adding 0.26 g of trifluoroethyl methacrylate (3FMA) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0092] (4) adding 1.5 g of sulfobetaine methacrylate (SBMA) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0093] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0094] (6) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0095] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0096] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named PSBMA-HCCM-3FMA;

[0097] (9) Using the obtained PSBMA-HCCM-3FMA hydrogel as an electrolyte material, together with the negative electrode and positive electrode of the zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0098] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0099] The negative electrode is a zinc foil negative electrode.

[0100] Comparative Example 2

[0101] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof, which is different from Embodiment 1 in that the surfactant used is hexadecyltrimethylammonium chloride (CTAC), and the specific steps are as follows:

[0102] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0103] (2) dissolving 2.12 g of hexadecyltrimethylammonium chloride (CTAC) surfactant in 30 mL of solution A at 100° C. to obtain solution B;

[0104] (3) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0105] (4) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0106] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0107] (6) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0108] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0109] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named PAM-CTAC-C18;

[0110] (9) Using the obtained PSBMA-CTAC-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of the zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0111] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0112] The negative electrode is a zinc foil negative electrode.

[0113] Comparative Example 3

[0114] This embodiment provides an amphiphilic hydrogel material and a preparation method thereof, which is different from the embodiment 1 in that the surfactant used is 1-hexadecyl imidazole (HI), and the specific steps are as follows:

[0115] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0116] (2) dissolving 2.12 g of 1-hexadecyl imidazole (HI) surfactant in 30 mL of solution A at 100° C. to obtain solution B;

[0117] (3) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution B and stirring at 100° C. for 10 minutes to obtain solution C;

[0118] (4) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution C, stirring and dissolving for 10 minutes to obtain a mixture D;

[0119] (5) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture D and cooling to room temperature to obtain a mixture E;

[0120] (6) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture E to obtain mixture F;

[0121] (7) Pour F into a sealed mold and place the entire mold in an oven at 70 °C for 1 hour to obtain hydrogel G, in which the hydrophobic polymer chains are cross-linked with the hydrophilic polymer chains;

[0122] (8) placing the prepared hydrogel in a mixed solution H of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining an amphiphilic hydrogel electrolyte I, which is named PAM-HI-C18;

[0123] (9) Using the obtained PAM-HI-C18 hydrogel as an electrolyte material, together with the negative electrode and positive electrode of the zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0124] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0125] The negative electrode is a zinc foil negative electrode.

[0126] Comparative Example 4

[0127] This embodiment provides a monophilic hydrogel material and a preparation method thereof, which is different from the embodiment 1 in that: no hexadecylpyridinium chloride monohydrate (HCCM) surfactant is used, and the specific steps are as follows:

[0128] (1) Using water as solvent and zinc sulfate as solute, a 1 mol / L electrolyte, i.e., cationic solution A, is prepared;

[0129] (2) adding 0.26 g of octadecyl methacrylate (C18) hydrophobic polymer chain monomer to the above solution A and stirring at 100° C. for 10 minutes to obtain solution B;

[0130] (3) adding 1.5 g of acrylamide (AM) hydrophilic molecular chain monomer to the above solution B, stirring and dissolving for 10 minutes to obtain a mixture C;

[0131] (4) adding 0.003 g of N,N'-methylenebisacrylamide (MBAA) crosslinking agent to the mixture C and cooling to room temperature to obtain a mixture D;

[0132] (5) adding 0.08% ammonium persulfate (APS) thermal initiator to mixture D to obtain mixture E;

[0133] (6) Pour E into a sealed mold and place the entire mold in an oven at 70°C for 1 hour to obtain hydrogel F, in which the hydrophobic polymer chains are not cross-linked with the hydrophilic polymer chains;

[0134] (7) placing the prepared hydrogel in a mixed solution G of 1 M ZnSO4 + 0.2 M MnSO4, and finally obtaining a monophilic hydrogel electrolyte H, which is named PAM;

[0135] (8) Using the obtained PAM hydrogel as an electrolyte material, together with the negative electrode and positive electrode of a zinc ion battery, to form a secondary aqueous zinc ion battery. This step can be achieved by a person skilled in the art using a method disclosed in the prior art. The positive and negative electrodes can be selected as follows:

[0136] The positive electrode uses an α-MnO2 pole piece. α-MnO2 powder, Ketjen black and polyvinylidene fluoride (PVDF) with a weight ratio of 7:2:1 are mixed and fully ground. Then N-methylpyrrolidone (NMP) solvent is added to the mixture and stirred to form a uniform slurry. The slurry is then coated on the surface of a carbon cloth (CC) substrate by coating. The coated CC substrate is dried in an oven at 60°C for 10 hours to produce the α-MnO2 / CC positive electrode.

[0137] The negative electrode is a zinc foil negative electrode.

[0138] Performance Testing

[0139] The amphiphilic hydrogel materials prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to linear sweep voltammetry and charge-discharge tests.

[0140] The linear sweep voltammetry method is as follows: titanium foil is used as the working electrode, zinc foil is used as the reference electrode and the counter electrode, and the amphiphilic hydrogel obtained in Examples 1-5 and Comparative Examples 1-3 is used as the electrolyte to assemble a soft-pack battery, and the electrochemical stability window (ESWs) of the electrolyte is obtained by testing with an electrochemical workstation.

[0141] The charge and discharge test is as follows: a soft-pack battery is assembled using an α-MnO2 / CC positive electrode, a zinc foil negative electrode, and the amphiphilic hydrogel obtained in Examples 1-5 and Comparative Examples 1-3 as electrolytes, and the battery is tested using a blue-electric test system. The results are shown in Table 1.

[0142] Table 1

[0143] Electrochemical stability window (V) Slope of zinc embedding potential (1.33V) curve Example 1 3.0 0.1 Example 2 3.0 0.3 Example 3 3.0 0.4 Example 4 2.9 0.3 Example 5 2.8 0.1 Comparative Example 1 2.6 0.5 Comparative Example 2 3.0 6.0 Comparative Example 3 3.0 3.0 Comparative Example 4 2.0 3.5

[0144] As can be seen from Table 1, the amphiphilic hydrogel electrolytes of Examples 1-5 achieve a wider electrochemical stability window when the slope of the zinc embedding potential curve is low. In the amphiphilic hydrogel electrolytes prepared in Examples 1-5, the trace amount of hydrophobic monomers enhances the binding force between the adjacent hydrophilic functional groups and water molecules, which widens the electrolyte electrochemical window, but changes in the quality of the hydrophilic and hydrophobic monomers and surfactant feeds will slightly change its electrochemical stability window; in addition, the introduction of the surfactant HCCM can effectively regulate the embedding of zinc ions into the manganese dioxide positive electrode material.

[0145] Comparative Example 1 changes the types of hydrophilic monomers and hydrophobic monomers. Compared with Example 1, the interaction between water molecules and hydrophilic functional groups in the amphiphilic hydrogel is weakened, and its electrochemical stability window is reduced; in addition, the effect of regulating zinc ions is also reduced, and the slope of the zinc embedding potential curve increases.

[0146] Comparative Example 2 introduces a pure carbon chain ionic surfactant CTAC. Compared with Example 1, the electrochemical stability window remains unchanged, but the strong repulsion of CTAC to zinc ions and hydrogen ions results in a large potential curve slope of 1.33V, making it almost impossible for zinc ion embedding to occur.

[0147] Comparative Example 3 introduces the pure imidazole ring surfactant HI. Compared with Example 1, the electrochemical stability window remains unchanged, but the strong attraction of HI to zinc ions and hydrogen ions results in a larger 1.33V potential curve slope, and the effect of regulating zinc ions is very weak.

[0148] Comparative Example 4 does not use the surfactant HCCM. Compared with Example 1, the hydrophobic segments cannot be introduced near the hydrophilic functional groups, resulting in the interaction between water molecules and hydrophilic functional groups in the gel not being enhanced, so the electrochemical stability window is extremely narrow (equivalent to the electrochemical stability window of ordinary water-salt solution); in addition, the pure hydrophilic gel cannot regulate zinc ions well, and the slope of the zinc embedding potential (1.33V) curve increases sharply.

[0149] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0150] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. An amphiphilic hydrogel electrolyte for an aqueous zinc ion battery, characterized in that: The hydrophilic segments in the hydrogel electrolyte are cross-linked with hydrophobic segments.

2. The amphiphilic hydrogel electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The hydrophilic segment refers to polyacrylamide.

3. The amphiphilic hydrogel electrolyte for aqueous zinc ion batteries according to claim 1, characterized in that: The hydrophobic segment refers to polyoctadecyl methacrylate.

4. A method for preparing an amphiphilic hydrogel electrolyte for an aqueous zinc ion battery according to any one of claims 1 to 3, characterized in that: include: 1) dissolving the hydrophobic polymer chain monomer and the hydrophilic molecular chain monomer in a cationic salt solution containing a surfactant in sequence; 2) adding a crosslinking agent and a thermal initiator in sequence; 3) sealing and heating the reaction to obtain a hydrogel; 4) placing the hydrogel prepared in 3) in a mixed solution of zinc ions and manganese ions to obtain an amphiphilic hydrogel electrolyte.

5. The method according to claim 4, characterized in that The hydrophobic polymer chain monomer refers to octadecyl methacrylate, the hydrophilic molecular chain monomer refers to acrylamide, and the surfactant refers to hexadecylpyridinium chloride monohydrate.

6. The method according to claim 5, characterized in that The cationic salt is zinc sulfate, the crosslinking agent is N,N-methylenebisacrylamide, and the thermal initiator is ammonium persulfate.

7. The method of claim 4, characterized in that 3), the heating reaction is carried out at 30-80°C for 1-3h.

8. The method of claim 4, characterized in that The mass ratio of the hydrophobic polymer chain monomer, the hydrophilic molecular chain monomer, the surfactant, the cross-linking agent and the thermal initiator is 0.20-0.40:1.5-3.0:2.0-4.0:0.003:0.

08.

9. An aqueous zinc ion battery, characterized in that: The amphiphilic hydrogel electrolyte for aqueous zinc ion batteries according to any one of claims 1 to 3 is used as the electrolyte.

10. The aqueous zinc ion battery according to claim 9, characterized in that: The negative electrode uses metal zinc foil as the negative electrode, and the positive electrode uses manganese dioxide as the positive electrode.